Hubungan Aktivitas Fisik dengan Kejadian Obesitas pada Usia Dewasa di Puskesmas Banyuanyar - Trisia Tya Nisa; Dewi Kartika Sari (Yayasan Literasi Sains Indonesia, 2023)
The obesity rate in the world is quite high, with as many as 1 million people. Obesity is mostly experienced by adults as many as 650 million people. This is due to low physical activity. The effects of obesity include diabetes and hearth disease. The study aimed to determine whether there is a relationship between physical activity and the incidence of obesity in adults at the Banyuanyar Public Health Center. This with a correlation design, uses a cross-sectional approach, data collection techniques use purposive sampling, a sampel of 85 responden, the instrument used to measure physical activity uses the Global Physical Activity Questionnaire (GPAQ) questionnaire and BMI is measured using the weight division formula. (kg) by the square of the height (). Of the univariate analysis shows that 47,1% of respondents were in the low category of physical activity, and 30,6% of respondents were in class 2 obesity. Bivariate results showed that the relationship between physical activity and the incidence of obesity in adulthood obtained a p-value of 0,007 (<0.05). There is a relationship between physical activity and the incidence of obesity in adults a the Banyuanyar Health Center.